Statistical evaluation of the quality of working life of employees in the russian federation - Vera V. Zholudeva; Nadezhda F. Melnichenko (Статистика и экономика)
Quality of life is one of the most important characteristics that reflects a comprehensive description of the level and living conditions. Nowadays quality of working life is an integral feature of “Quality of Life”. Quality of working life identifies working conditions and labor management. The quality of working life allows us to determine the working conditions, its organization from the perspective of the optimal realization of the abilities of employees.The article analyzes the domestic approaches to the definition and evaluation of the quality of working life. The conducted research allowed the authors to draw the following conclusions: the quality of working life is characterized by a multitude of indicators, and the required condition for studying the quality of working life is the development of techniques that allow the evaluation of the studied category.The goal is to evaluate the quality of working life in Russia.Methods. A number of indicators are presented to estimate the quality of working life of employees in the Russian Federation. According to the authors, those indicators are employment, labor safety, work safety, salary, and competence level and workforce productivity. The analysis that is based on data from Federal State Statistics Service has been done in view of gender factors and federal district differences. According to this analysis, the general part of workforce has jobs with harmful or dangerous working conditions. Extractive and process industries are considered the most hazardous.The article describes the method of integrated assessment of working life quality, based on the study of social and labor sphere of the Federal districts of Russia. Based on this author’s method, the integral indicators of the quality of working life of the population of the Russian Federation in the context of Federal districts are calculated and analyzed and the rating of each of them is determined.Results. The article notes that the quality of working life reflects not only the working conditions and its payment, but also the relations in the working collective, the motivation of the personnel to work. The most important motivational factors and characteristics of the socio-psychological climate of the enterprise are determined. The set of indicators, proposed by the authors and the methods of assessing the quality of the working life of the population can be useful to local governments for determining the rating of the quality of working life of officers in municipalities, and thus for making various managerial decisions.